2020
DOI: 10.1371/journal.pone.0224006
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparities in antenatal care utilization in Indonesia

Abstract: Introduction The main strategy for decreasing maternal morbidity and mortality has been antenatal care (ANC). ANC aims to monitor and maintain the health and safety of the mother and the fetus, detect all complications of pregnancy and take the necessary actions, respond to complaints, prepare for birth, and promote a healthy lifestyle. This study aims to analyze interregional disparities in �4 ANC visits during pregnancy in Indonesia. Methods Data was acquired from the 2017 Indonesian Demographic and Health S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 41 publications
14
54
0
Order By: Relevance
“…Therefore, the working husband will have the financial capacity to pay for ANC services [34]. Family income and ANC fees are related to access to ANC services [5,29]. The results of previous research conducted by Othman on 460 mothers in the City of Sana'a, Yemen are the same as the results of the study in this study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, the working husband will have the financial capacity to pay for ANC services [34]. Family income and ANC fees are related to access to ANC services [5,29]. The results of previous research conducted by Othman on 460 mothers in the City of Sana'a, Yemen are the same as the results of the study in this study.…”
Section: Discussionsupporting
confidence: 67%
“…Health services ranging from examinations of pregnant women/ANC, delivery assistance by trained health workers in health facilities, care for mothers and babies after delivery to care in case of complications. ANC is done at least 4 times during pregnancy [5]. This is done to provide protection for pregnant women and the fetus by early detection of risk factors, taking precautions, and treating complications of pregnancy early.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted in Malawi has found a significant association between the health facility and the utilization of PNC services. Other Ethiopia studies have demonstrated that physical accessibility plays an essential variable in health service utilization (Kim et al, 2019;Tarekegn et al, 2014). Access to the health facility is related to the costs incurred, which is influenced by having transportation to the health facility, which is considered expensive.…”
Section: Discussionmentioning
confidence: 99%
“…26 It remains as a challenge of physical access since Indonesia has archipelagic characteristics. 12,27 Previous studies have informed the difficulty of accessing health services in border areas and islands in Indonesia. 28,29 This current study pointed out that young people who had enough knowledge of pregnancy danger signs had a better possibility of utilizing healthcare facilities.…”
Section: Discussionmentioning
confidence: 99%
“…ANC in pregnant young people is also necessary for early detection of problems in pregnancy. 12 Based on the background description, this research is aimed to analyze the determinants of healthcare childbirth in Indonesian young people.…”
Section: Significance For Public Healthmentioning
confidence: 99%